PENYULUHANPEMANFAATAN KOTORAN HEWANSEBAGAIPAKANLELE - Indah Susantun (UII, 2014)
Everyday there is more and more catfish farmers who complained of the highprice of feed, so it can make the benefits getting low. High feed prices is the mainproblem faced by catfish farmers, as was the case with catfish farmers in the DusunBakalan, Boto village, subdistrict Wonosari, Klaten regency, Central Java province.Alternative new catfish feed by processing its own and utilize livestock manure providesbenefits that catfish farmers will be protected from harm and will get a catfish feed withcheap and free.